Comparative study of type 1 tympanoplasty with and without gel-foam in the middle ear - Kiran, G. Abhinav; Rao, Y. Prabhakara; Priyanka, B. Shanthi; ., Supreety (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic suppurative otitis media is a widespread disease for which tympanoplasty is frequently undertaken. Gel-foam may cause adhesions and fibrosis and improper packing may physically alter the structure of the tympanic membrane leading to failure of tympanoplasty. The graft can be placed without any middle ear supporting agent wherein the graft is held in position by the surface tension between the novel graft placed and the remnant tympanic membrane. The objectives of this study were to assess the graft uptake and hearing improvement following type 1 tympanoplasty with gel-foam in the middle ear and without gel-foam in the middle ear and to compare and assess results. Methods: This was a randomized control trial done for a period of one year conducted in the department of ENT, at a tertiary referral hospital. 40 patients with dry perforation underwent type 1 tympanoplasty without gel-foam in the middle ear and 40 patients with dry perforation underwent type 1 tympanoplasty with gel-foam in the middle ear. Post-operative follow-up was done to look for graft uptake. Hearing assessment by pure tone audiometry was done 90 days post-operatively. Results: Graft uptake was 82.5% in type 1 tympanoplasty without gel-foam in the middle ear and 85% with gel-foam in the middle ear. Both types of surgeries had significant hearing improvement. Conclusions: Graft uptake is equally good in cases with gel-foam and without gel-foam. Hearing gain is comparable in both groups of patients.